Developing Listening Fluency through Supported Extensive Listening Practice. (December 2019) - Chang, Anna; Millett, Sonia; Renandya, Willy Ardian
Although second language listening has become a rather active area of research in the past ten years, some topics such as listening fluency development and extensive listening (EL) have not received much attention. The purpose of the present study is to examine the levels of listening support that might be needed to facilitate L2 learners' listening fluency development. Sixty-nine EFL college students completed a full intervention through one of the three modes: (1) listening only (LO), (2) reading only (RO), and (3) reading while listening plus listening only (RLL). Ten level-1, 10 level-2 and 8 level-3 (audio) graded readers were used as the study materials within three 13-week periods. Listening tests were given before the intervention (pre-test) and after they finished each level of the texts (post-tests 1, 2 and 3). The research questions addressed effect sizes of the scores' changes from the pre-test to each of the post-tests in each group on their comprehension of practised and unpractised texts. The results show that in comprehending the practised texts, the LO and RLL groups could comprehend the more complicated texts at faster speech rates and also maintain higher levels of comprehension. When listening to the unpractised texts, the RLL group could do as well as they did on the practised texts, but the LO group could process the more difficult texts at faster speech rates without decreasing their comprehension levels. As predicted, the RO group performed poorly on the tests. Pedagogical implications for facilitating the effectiveness of extensive listening practice are discussed.